Two new species and key to four species of the genus Humphaplotropis from China (Orthoptera: Pamphagidae, Pamphaginae) - Zhi, Yong-Chao; Shi, Jian-Ping; Dai, Li (Zootaxa, 2015)
Two new species i.e.: Humphaplotropis xiai sp. nov. and Humphaplotropis hebeiensis sp. nov. of the genus Humphaplotropis Xiao, Yin et Yin, 2013, are described from Hebei and Jiangsu, China in this paper. The new species Humphaplotropis xiai sp. nov. differs all known species of the genus by the abdomen like sawtooth in lateral view. The new species Humphaplotropis hebeiensis sp. nov. is similar to Humphaplotropis culaishanensis Lin, Cao et Yin, 2014, but differs from the latter by: lateral carinae of frontal ridge parallel; anterior margin of pronotum with acute angular in the middle, the apex reaching the hind margin of eyes; tegmina wider, cover 4/5 tympanum. Hind tibia yellow brown on upper side; epiphallus with 44 spikes, ancorae oblique inward distinctly, both posterior projections shorter than median projection. Type specimens are deposited in the Shanghai Entomological Museum, C.A.S., Shanghai and Natural Museum of Hebei University, Baoding, Hebei China respectively.